Exploration of Self-regulated Learning through Edmodo - Trisniawati Trisniawati; Nelly Rhosyida; Mahmudah Titi Muanifah; Ida Megawati; Sri Adi Widodo; Ana Fitrotunisa; Beti Istanti Suwandayani; Martalia Ardiyaningrum (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
The purpose of this paper is to describe mathematics self-regulated learning of elementary school teacher education students. This type of research used qualitative approach. The subject research is taken from 2nd semester student’s primary school teacher education of 2020 academic year. Instrument used in this research is questionnaire. The questionnaire is used to know the student's self-regulated in mathematics learning with six factors namely (a) independence of others, (b) have self-confidence, (c) behaving dicipline, (d) having a sense of responsibility, (e) behaving based on their own initiative, and (f) perform self-control. Based on the results of the research, it can be concluded that self-regulated learning though edmodo is in the high category.